Zakat Produktif: Pemberdayaan umat melalui zakat produktif - Nurhaliza, Devina Binti (Maliki Interdisciplinary Journal, 2024)
Productive zakat is one form of zakat that can be used for the empowerment of the Muslim community. Productive zakat aims to provide business capital to the mustahik in the form of interest-free loans or business capital that can improve their well-being and economic empowerment. In its implementation, productive zakat can be carried out through various programs and institutions such as zakat management agencies, Islamic microfinance institutions, and programs for the empowerment of micro, small, and medium-sized enterprises (MSMEs) through productive zakat.The empowerment of the Muslim community through productive zakat has several benefits, including increasing economic independence, reducing poverty, and improving the well-being of the community. However, there are challenges in its implementation, such as the need for guidance and training, monitoring and evaluation, as well as raising awareness and participation of the community in giving productive zakat.In the distribution of productive zakat, it is important to provide guidance and training to the mustahik to ensure that they can manage the business capital effectively. This can be done through direct assistance from Islamic religious counselors in zakat management agencies. The goal is to enable the mustahik to improve their economic conditions and eventually become muzakki.